Perbandingan Metode SAW dan Topsis pada Sistem Pendukung Keputusan Pemilihan Calon Guru di SMA Negeri 16 Medan - Eggy Ryan Agvi Riansyah; Evi Prasetyani; Habibullah; Waisul Kurni; Perani Rosyani (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
The idea of ​​decision assistance programs is growing rapidly today. There are many techniques that can help decision making. The TOPSIS and SAW approaches can both be used to address Multi-Attribute Decision Making (MADM) problems. This is due to the fact that the method is simple, easy to understand, computationally efficient, and capable of calculating the relative performance of decision-alternatives in a straightforward mathematical form. The challenge of this study was to complete a particular MADM example where it might be challenging to choose between the SAW procedure and the TOPSIS method which is more relevant. As a result, a sensitivity test was carried out to identify the best strategy to resolve disputes between SAW and TOPSIS. The purpose of this problem is to assist everyone in making a decision based on the best alternative value. The Multi-Attribute Decision Making (MADM) problem was solved through the Sensitivity Test technique at first.